IMPLEMENTASI MEDIA POSTER UNTUK MENINGKATKAN PEMAHAMAN MATERI IPA SISWA SD - Bhala, Maria Regina; Dinatha, Ngurah Mahendra; Pare, Prisko Yanuarius Djawaria; Kua, Maria Yuliana (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to apply poster media to increase student’s understanding of science learning at SD Inpres Dhereisa Elementary School. The problem found by researchers was the lack of use of science learning media for student’s, which had an impact on student’s low learning outcomes. The method used in this research is Classroom Action Research (CAR) design. The subjects in this research were 21 grade 5 student’s at SD Inpres Dhereisa. The data collection technique used was an observation sheet on student activities in science learning using posters on human respiratory system materials. The problem found by researchers was the lack of use of science learning media for student’s, which had an impact on student’s low learning outcomes. The results of the research show that there is an increase in student activity in learning science using posters. Student activities that experienced an increase were observing material on the respiratory system in humans using posters, which increased by 24%. Explaining activities increased by 38%, activities responding to and answering questions increased by 34%, activities doing group assignments increased by 28%, and activities presenting group assignments increased by 33% using poster media. Based on student’s activities using poster media, it is proven that poster media can increase student’s understanding of science material